2017
DOI: 10.1007/s40271-017-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-Reported Palliative Care-Specific Health Classification System: The POS-E

Abstract: BackgroundGeneric preference-based measures are commonly used to estimate quality-adjusted life-years (QALYs) to inform resource-allocation decisions. However, concerns have been raised that generic measures may be inappropriate in palliative care.ObjectiveOur objective was to derive a health-state classification system that is amenable to valuation from the ten-item Palliative Care Outcome Scale (POS), a widely used patient-reported outcome measure in palliative care.MethodsThe dimensional structure of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…2 The POS has undergone psychometric evaluation using traditional methods such as reliability, 1 exploratory factor analysis, 3,4 and confirmatory factor analysis. 3 Rasch analysis has been used with selected POS items to develop a palliative care health classification system and supported its internal validity 5 ; however, as yet, Rasch analysis has not been used with the IPOS and conversion tables have not been produced. Cognitive interviews evaluating the acceptability and utility of the IPOS showed that the questionnaire was easy to comprehend, acceptable, and not burdensome to complete.…”
Section: Introductionmentioning
confidence: 99%
“…2 The POS has undergone psychometric evaluation using traditional methods such as reliability, 1 exploratory factor analysis, 3,4 and confirmatory factor analysis. 3 Rasch analysis has been used with selected POS items to develop a palliative care health classification system and supported its internal validity 5 ; however, as yet, Rasch analysis has not been used with the IPOS and conversion tables have not been produced. Cognitive interviews evaluating the acceptability and utility of the IPOS showed that the questionnaire was easy to comprehend, acceptable, and not burdensome to complete.…”
Section: Introductionmentioning
confidence: 99%
“…We considered ≥ 0.70 as acceptable [31,40]. We assessed the Chi Square statistic (χ2) with Bonferroni adjusted signi cance levels (alpha value = 0.05/number of items in the original domain), but did not consider it a determinant of model t given its sensitivity to large sample sizes, which can overestimate lack of model t [41].…”
Section: Rasch Model Fit: We Evaluated Model T Statistics Including Cmentioning
confidence: 99%
“…Nevertheless, moving beyond generic health measures such as EQ-5D to form QALYs, is an active area of investigation in evaluation of palliative and end of life care, with research moving in two directions, employing differing value judgements. The first remains within the general QALY paradigm whilst relaxing the value judgement around use of generic health measures, in favour of using a 'health' measure that reflects health issues faced by those receiving palliative care (11). The second is more radical, questioning more of the value judgements associated with QALY maximisation (9) and shifting focus towards capability wellbeing amongst those at end of life (12)(13)(14) and persons close to them (15).…”
mentioning
confidence: 99%
“…The first tranche of research builds on an existing, widely used measure, the Palliative care Outcomes Scale (POS) and its forerunner, the Support Team Assessment Schedule (16), to develop a new scale, the POS-E. POS-E has been derived from the existing ten-item, five level POS (11). This is a point at which practical considerations enter: the POS scale itself is too large to feasibly produce a full value set, and so a derived seven-item scale has been generated, with each item having smaller numbers (two or three) of levels (11) (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation